Reflections on the readings of Sundays and feasts: December 2022-February 2023 - Sobb, Joseph (The Australasian Catholic record, 2022)
Images, unusual and attractive, harsh and provocative, abound in the first and gospel readings. There are evocative themes and literary allusions between the readings: the phrase, 'in those days', in the Gospel (Matt 3:1) introducing John the Baptist, echoes the prophetic proclamation, 'on that day', introducing the descendant of David in the first reading (Isa 11:10); and the concluding words of the second reading (Rom 15:9) echo the concluding words of the responsorial psalm (Ps 71/72:17); finally, the themes of justice and righteousness in the first reading and the psalm lie behind the strong words of John the Baptist's address to the Pharisees and Sadducees, which call for a change of heart, 'repent' (Matt 3:2 and 8).